A model of relationship between climate and soil factors related to oxalate content in porang (Amorphophallus muelleri Blume) corm - SERAFINAH INDRIYANI; ENDANG ARISOESILANINGSIH; TATIK WARDIYATI; HERY PURNOBASUKI (Society for Indonesian Biodiversity, 2011)
Indriyani S, Arisoesilaningsih E, Wardiyati T, Purnobasuki H (2011) A model of relationship between climate and soil factors related to oxalate content in porang (Amorphophallus muelleri Blume) corm. Biodiversitas 12: 45-51. The abiotic environment as well as the biotic environment, involved climate and soil affect directly or indirectly to plant growth as well as plant substance. The objective of the research was to obtain a model of relationship between climate and soil factors related to oxalate content in porang corm. Porang corms were collected from five locations of porang agroforestry in East Java. The locations were (i) Klangon Village, Saradan Subdistrict, Madiun District; (ii) Klino Villlage, Sekar Subdistrict, Bojonegoro District; (iii) Bendoasri Village, Rejoso Subdistrict, Nganjuk District;(iv) Sugihwaras Village, Nggluyu Subdistrict, Nganjuk District and (v) Kalirejo Village, Kalipare Subdistrict, Malang District.Geography variable consist of altitude. Climate variables consist of percentage of radiation, temperature and rainfall. Soil variables consist of electrical conductivity, pH, soil specific gravity, soil organic matter, available of calcium, and cation exchange capacity (CEC). Vegetation variables consist of species of plant tree and percentage of coverage. Porang vegetative growth variables consist of plant height, number of bulbil, canopy diameter, and petiole diameter. Corm variables consist of corm diameter, corm weight, and corm specific gravity. Oxalate variables consist of total oxalate, soluble oxalate, insoluble oxalate, and density of calcium oxalate crystal.Oxalate contents were measured based on AOAC method. All of variables were collected from first to fourth growth period of porang. Data were analyzed by smartPLS (Partial Least Square) software. The results showed that there were significantly direct effect between altitude and temperature, altitude and CEC of soil, temperature and CEC of soil, altitude and percentage of coverage, temperature and percentage of coverage, CEC of soil and percentage of coverage, CEC of soil and petiole diameter, petiole diameter and corm diameter, and petiole diameter and corm oxalate content. There were no significantly direct effect among altitude, temperature, percentage of coverage and petiole diameter; and among corm total oxalate, soluble oxalate, insoluble oxalate, and density of calcium oxalate crystal and corm diameter. The value of Goodness of Fit of the developing model was RÂ²=0.99.Key words: corm, climate, model, oxalate, smartPLS, porang, soil.